Always on Sunday - Harpur, Tom (Toronto : Oxford University Press, 1988)
A collection of the author's columns originally published in the Toronto Sunday Star.
Includes bibliographical references
Keywords: Christian life -- 1960-; Christianity -- 20th century; Church and the world